(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Culture means people’s pattern of life customs, ethics and their social behaviour. Culture is passed on from the ancestors to the next generation. It has a strong influence on who we are. This pattern of life of the Australian Aborigines was disturbed with the advent of the English Convicts and Mariners. Among the colonies of the British, Australia was a different colony. It was initially considered as a penal colony, an open prison. Australia became a distant colonial territory where the English sent the convicts. This created devastating impact on the indigenous population which had developed their culture 60,000 years back. As part of the colonising process several policies were formulated to civilize the aborigines. One among them was the Assimilation Policy. It was a policy that was thirsted on the Aborigines to adapt western culture.